Dampak Peningkatan Bisnis E-Commerce Dalam Pengembangan Mutu Transportasi Logistik Graha Trans - Alia Ingrid Pradina; Bella Trisya Almira; Natasya Putri Khalistia; Siti Sahara (Lembaga Pengembangan Kinerja Dosen, 2023)
The current digital era has an impact on e-commerce businesses. This also has an impact on the growth of logistics transportation companies to meet customer needs. Graha Trans experienced a positive impact from the booming e-commerce business. Quality assurance is needed to measure the success of a logistics transportation company and become a reference for improvement. The research method used is a literature study by collecting various related references related to the development of the quality of Graha Trans's logistics transportation. The results of the research are that Graha Trans carries out quality assurance by providing periodic checks on vehicles, providing training for employees to carry out standard operating procedures and creating services that make it easier for customers to track goods.